Pengaruh Jumlah Penduduk dan Pertumbuhan Ekonomi terhadap Pendapatan Asli Daerah (PAD) di Kota Medan - Sebrina Handayani; Yunita Sari Rioni (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to examine the extent to which population and macroeconomic aspects, particularly population and economic growth, have an impact on Local Own Revenue (PAD) in Medan City in the 2016-2023 period. This research applies quantitative research methods with multiple linear regression analysis methods. This research was conducted at the Medan City government with secondary data published by the Directorate General of Fiscal Balance (DJPK) and the Medan City Statistics Center (BPS). The results of hypothesis testing show that the sig. value of the population variable is 0.001 <0.05 where the t value is 7.150> t table value 2.571. The sig value of the economic growth variable is 0.003 < 0.05 where the t value is 5.338 < the t table value of 2.571. The sig value. population and economic growth variables simultaneously amounted to 0.002 < 0.05 where the value of f count 27.085 > the value of f table 5.143. Based on the data from the research conducted, it is found that the population of Medan City has a positive and significant effect on Regional Original Revenue (PAD) in Medan City. Economic growth in Medan City has a positive and significant effect on Regional Original Revenue (PAD) in Medan City. Population and economic growth in Medan City have a positive and significant effect simultaneously on Regional Original Revenue (PAD) in Medan City.